A remark about actions of lattices on free groups - Bridson, M; Farb, B (2001)
Every homomorphism from an irreducible, noncocompact lattice in a higher-rank semisimple Lie group to the outer automorphism group of a free group must have a finite image. (C) 2001 Elsevier Science B.V. All rights reserved.